Growth of SrTiO3 bulk single crystals using edge-defined film-fed growth and the Czochralski methods. Issue 25 (7th July 2015) - Guguschev, Christo; Galazka, Zbigniew; Kok, Dirk J.; Juda, Uta; Kwasniewski, Albert; Uecker, Reinhard
<x xml:space="preserve">Abstract</x> Instability issues solved for SrTiO3 grown from stoichiometric melts.